A DWT-DCT-SVD Based Enhancement Technique for Low Contrast Satellite Images (International Journal of Engineering and Computer Science, 2016)
Satellite images are used in many applications such as astronomy, geographical information system and geosciences. They are having narrow range of brightness values and contain low dynamic region of intensity values thus there is a need for enhancement. The paper presents a contrast and brightness enhancement approach based on Discrete Wavelet Transform, Discrete Cosine Transform and Singular Value Decomposition (DWT-DCT-SVD) technique for quality improvement of low contrast satellite images. The input image is decomposed into four frequency sub bands through DWT of each band R, G and B of input image. DCT is applied to LL band of DWT to protect illumination information and then obtains singular value matrix of low frequency components of DCT and finally, it reconstructs the enhanced image by applying IDWT, IDCT and ISVD. Singular value matrix gives intensity information of particular image and any change in singular values directly change in image intensity. The experimental results show superiority of proposed technique in terms of PSNR, MSE, Mean and Variance over other techniques